UPAYA PT. INDAH KIAT PULP AND PAPER DALAM PELAKSANAAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) TUJUAN 4 &TUJUAN 8 - Maulidia, Nur; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Sustainable Development Goals is a world development agenda announced by the United Nations in 2015. This agenda is a universal call to improve human life wherever they are. Implementing sustainable development goals is the responsibility of all groups, including government, organizations, academics and business actors. One of the companies that has contributed to the implementation of the SDGs is PT Indah Kiat Pulp and Paper. The main focus of the SDGs is on goal 4 and goal 8 This research uses the theory of Corporate Social Responsibility and the group level of analysis. This theory explains the responsibilities of companies, which do not only seek profit, but must still pay attention to people and the environment around their operations. The research method used is a qualitative method with data collection techniques obtained from interviews and various reading sources. The results of this research show that PT Indah Kiat has implemented the SDGs through its CSR activities. Based on the theory of Corporate Social Responsibility put forward by John Elkington, there are three basic principles, namely profit, people and planet. The first is profit, where the company seeks to maintain and protect its image regarding its market share. Second is the people principle which is carried out through vocational education programs, scholarships and smart homes as a form of contribution to SDGs goal 4 and integrated agricultural training programs, empowering MSMEs and strapping business collaborations which implement goal 8. Third, the planet principle which the company implements by making efforts clean industrial activities to protect the environment. Kata Kunci: Sustainable Development Goals, PT Indah Kiat Pulp and Paper, Goals 4, Goals 8, CSR